2012
DOI: 10.3892/etm.2012.694
|View full text |Cite
|
Sign up to set email alerts
|

Detecting KRAS mutations in peripheral blood of colorectal cancer patients by peptide nucleic acid clamp PCR

Abstract: We investigated the effectiveness of peptide nucleic acid (PNA) clamp PCR for detecting KRAS mutations in peripheral blood samples of colorectal cancer (CRC) patients. We compared KRAS point mutations between tumour tissue and blood samples. Forty-two patients were included in this study. We observed KRAS mutations in formalin-fixed, paraffin-embedded tissues by PCR direct sequencing and in blood samples by PNA clamp PCR. KRAS point mutations were detected in primary tumour tissue samples of 13 patients (31.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…A total of 5032 studies were excluded after primary screening, and 94 articles were selected for further assessment of eligibility. By rigorous evaluation, 28 studies met the inclusion criteria and were included in our present meta‐analysis. In the study reported by Taly and another study by Xu, KRAS status was detected by two different methods, and Morgan detected KRAS status both in serum and plasma, and the data from two different methods and two samples were analyzed as two independent studies.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 5032 studies were excluded after primary screening, and 94 articles were selected for further assessment of eligibility. By rigorous evaluation, 28 studies met the inclusion criteria and were included in our present meta‐analysis. In the study reported by Taly and another study by Xu, KRAS status was detected by two different methods, and Morgan detected KRAS status both in serum and plasma, and the data from two different methods and two samples were analyzed as two independent studies.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier procedure for sequencing the resistant markers from the viral isolate takes several days; however, PNA‐mediated PCR technique takes only few hours. PNA–PCR clamping technique has also been used in the detection of EGFR mutations in the circulating free DNA, BRAF V600E Mutation with Thyroid Tissue, KRAS mutations in peripheral blood of colorectal cancer patients, and T790M Epidermal Growth Factor Receptor Mutation . The natural diets of larval marine animals and Japanese eel leptocephali were also investigated using PNA‐directed PCR clamping …”
Section: Applicationsmentioning
confidence: 99%
“…Cel ten może zostać osiągnięty różnymi metodami, na przykład poprzez pozytywną selekcję zmutowanej sekwencji DNA z wykorzystaniem starterów PCR specyficznych dla poszukiwanego allelu (ASP-PCR, allele-specific primer PCR), hybrydowych sond fluorescencyjnych selektywnie amplifikujących i wykrywających zmutowany allel (Scorpion-ARMS, Scorpion Amplified Refractory Mutation System), a także poprzez wykorzystanie różnic w temperaturze topnienia homo-i heterodupleksów DNA (COLD-PCR, CO-amplification at Lower Denaturation temperature-Polymerase Chain Reaction) [21][22][23]. Selekcja zmutowanego allelu bywa też negatywna i dokonuje się poprzez blokowanie amplifikacji DNA typu natywnego, na przykład przez użycie antysensownych cząsteczek kwasu peptydonukleinowego (PNA, peptide nucleic acid) w metodach PNA-LNA PCR clamp, PNA clamp oraz PNA-SmartAmp2 czy też eliminację DNA o sekwencji natywnej za pomocą enzymu restrykcyjnego (ME-PCR, mutant-enriched PCR) [24][25][26][27].…”
Section: Allelospecyficzna Amplifikacjaunclassified